117 Functionality of a novel consensus bacterial 6-phytase variant in enhancing phosphorus digestibility in gestating and lactating sows. (30th November 2020) - Velayudhan, Deepak; de Grave, Xandra Benthem; Waller, Katie; Marchal, Leon; Dersjant-Li, Yueming
Abstract: Two experiments were conducted to determine the efficacy of phytase on apparent total tract digestibility (ATTD) of phosphorus (P) in gestating and lactating sows. In Exp. 1, a total of 40 sows (parity 2–6) at d 78 of gestation were randomly assigned, based on parity, over 4 experimental diets. In Exp. 2, 40 sows (parity 2.0–6.0) at d 4 of lactation were randomly assigned based on parity, over 4 experimental diets. Both studies had a positive control (PC) diet with adequate levels of calcium (Ca) and digestible P (6.5 and 2.5 g/kg and 7.0 and 3.2 g/kg for gestation and lactation diets, respectively), a negative control (NC) diet with low Ca and digestible P levels (5.0 and 1.0 g/kg and 5.0 and 1.5 g/kg for gestation and lactation diets, respectively), and NC supplemented with a novel consensus bacterial 6-phytase variant (PhyG) or a commercial Buttiauxella sp. phytase (PhyB), both at 500 FTU/kg. Diets were corn, soybean meal and sunflower meal based (phytate P of 3.0 g/kg) with restricted feeding during gestation and ad libitum during lactation. In both studies, fecal samples were collected after an adaptation of 14 d on 4 successive days to determine ATTD of P. Data were analyzed using ANOVA, treatment mean comparison using Tukey test using JMP 14. In addition, data from the Exp. 1 and 2 were pooled to further investigate their combined effect, using trial as random effect. In both studies, supplementation of both phytases improved (P < 0.05) ATTD of P vs NC. With data combined from two trials, sows fed PhyG showed greater (P < 0.05) ATTD of P when compared those fed PhyB. In conclusion, PhyG at 500 FTU/kg showed a greater ATTD of P in sows when compared to the PhyB at 500 FTU/kg, when data combined from two trials.